2000
DOI: 10.1016/s0893-133x(99)00091-3
|View full text |Cite
|
Sign up to set email alerts
|

Increased Temporal Cortex ER Stress Proteins in Depressed Subjects Who Died by Suicide

Abstract: Regulation of ER stress proteins, such as the 78-kilodalton glucose regulated protein (GRP78) by chronic treatment with mood stabilizing drugs suggests that this family of proteins may be involved in the pathophysiology of mood disorders. Indeed, increased levels of GRP78, GRP94, and calreticulin, a third member of the ERCurrent theories of the pathophysiology of mood disorders suggest that prolonged increases in glucocorticoid levels, likely the result of prolonged environmental stress, lead to biochemical ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
60
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 24 publications
(18 reference statements)
4
60
0
Order By: Relevance
“…23) In postmortem brain studies, increased levels of endoplasmic reticulum stress-related proteins such as GRP78, GRP94, and calreticulin have been found in the temporal cortex of subjects with major depressive disorder who died of suicide. 5) In corticosterone-treated animal depression models, increased levels of GRP78 and other endoplasmic reticulum stress-related proteins have been reported in the dentate gyrus and other region. 6,24) These reports suggest that neuronal cell death and endoplasmic reticulum stress may be involved in the pathogenesis of depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23) In postmortem brain studies, increased levels of endoplasmic reticulum stress-related proteins such as GRP78, GRP94, and calreticulin have been found in the temporal cortex of subjects with major depressive disorder who died of suicide. 5) In corticosterone-treated animal depression models, increased levels of GRP78 and other endoplasmic reticulum stress-related proteins have been reported in the dentate gyrus and other region. 6,24) These reports suggest that neuronal cell death and endoplasmic reticulum stress may be involved in the pathogenesis of depression.…”
Section: Discussionmentioning
confidence: 99%
“…5) Furthermore, in a rodent depression model, endoplasmic reticulum stress-related proteins were increased and these were attenuated by an antidepressant. 6) Recently, we have reported that restraint stress increases in the expression of endoplasmic reticulum stress-related genes in the mouse brain.…”
mentioning
confidence: 99%
“…The first evidence was detection of ER chaperones such as HSPA5, HSP90B1 and CALR as target genes of a mood stabilizer, valproate, using differential display (Wang et al 1999). Subsequently, increased expression of ER chaperones in the temporal cortex of depressed subjects who died by suicide was reported (Bown et al 2000). One microarray study using postmortem brain samples showed altered expression of HSP90B1 (gp96) in the bipolar disorder patients (Jurata et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…HSP90B1 expression is induced by treatment with valproate and lithium (Shao et al 2006) and its expression is altered in the postmortem brain of bipolar disorder patients (Bown et al 2000). The HSP90B1 gene is located on 12q23.3.…”
Section: Introductionmentioning
confidence: 99%
“…calreticulin) that assist in the folding of proteins in the endoplasmic reticulum (ER) [Bown et al, 2000[Bown et al, , 2002Chen et al, 2000;Kim et al, 2005]. Calreticulin is a multifunctional protein that acts as a major Ca(2þ)-binding storage protein in the lumen of the ER.…”
Section: Introductionmentioning
confidence: 99%